Upper Limb Swelling and Ipsilateral Recurrent Pleural Effusions in a Patient on Maintenance Haemodialysis: An Uncommon Aetiology Unveiled (Bangladesh Renal Journal, 2026)
Central venous stenosis is an established and often under-appreciated complication among patients undergoing haemodialysis, specially, among those with history of central venous catheter insertions. Patients may present with unilateral arm and hemi-facial swelling and recurrent ipsilateral pleural effusions. Prolonged bleeding after dialysis sessions and inadequate dialysis may raise the suspicion of central venous stenosis. A middle aged man with end-stage renal disease on maintenance haemodialysis through arterio-venous fistula, who was on anti-tuberculosis treatment, presented for right upper limb swelling and recurrent right sided pleural effusions. His haemodialysis was initiated through jugular venous catheters. Computed tomography (CT) venography confirmed right brachiocephalic vein stenosis and he was sent to vascular surgery for intervention.Bang. Renal J. 2026; 8(1): 35-37